Treatment and long-term outcome in primary distal renal tubular acidosis. Issue 6 (18th February 2019) - Lopez-Garcia, Sergio Camilo; Emma, Francesco; Walsh, Stephen B; Fila, Marc; Hooman, Nakysa; Zaniew, Marcin; Bertholet-Thomas, Aurélia; Colussi, Giacomo; Burgmaier, Kathrin; Levtchenko, Elena; Sharma, Jyoti; Singhal, Jyoti; et al.
Abstract: Background: Primary distal renal tubular acidosis (dRTA) is a rare disorder, and we aimed to gather data on treatment and long-term outcome. Methods: We contacted paediatric and adult nephrologists through European professional organizations. Responding clinicians entered demographic, biochemical, genetic and clinical data in an online form. Results: Adequate data were collected on 340 patients (29 countries, female 52%). Mutation testing had been performed on 206 patients (61%); pathogenic mutations were identified in 170 patients (83%). The median (range) presentation age was 0.5 (0–54) years and age at last follow-up was 11.0 (0–70.0) years. Adult height was slightly below average with a mean (SD score) of −0.57 (±1.16). There was an increased prevalence of chronic kidney disease (CKD) Stage ≥2 in children (35%) and adults (82%). Nephrocalcinosis was reported in 88%. Nephrolithiasis was more common with SLC4A1 mutations (42% versus 21%). Thirty-six percent had hearing loss, particularly in ATP6V1B1 (88%). The median (interquartile range) prescribed dose of alkali (mEq/kg/day) was 1.9 (1.2–3.3). Adequate metabolic control (normal plasma bicarbonate and normocalciuria) was achieved in 158 patients (51%), more commonly in countries with higher gross domestic product (67% versus 23%), and was associated with higher height and estimated glomerular filtration rate. Conclusion: Long-term follow-up from this large dRTA cohort shows an overall favourable outcome with normal adult height for most and no patient with CKD Stage 5. However, 82% of adult patients have CKD Stages 2–4. Importance of adequate metabolic control was highlighted by better growth and renal function but was achieved in only half of patients.